Control algorithm for shunt active filter based on Fryze power theory - Hashad منصور; Al-Ayeb طارق (Journal of Pure & Applied Sciences, 2021)
Active filters (AF) based on the Akagi instantaneous power theory, proposed in the early 1980s, are the most popular among researchers in this field, dozens of articles are published each year. This theory is mainly based on the Clarke transformation of a three-phase system, then the determination of the active and reactive instantaneous power in the alpha and beta systems, so on this basis, the AF currents are determined, next by using the Clarke inverse transformation, the reference currents for AF control algorithm are done. Shunt AF in the ideal case make the compensated mains current, sinusoidal, balanced and in phase with the voltage, i.e. improving the power factor. The article describes the shunt AF control strategy according to Fryze instantaneous theory, which he published in the early 1920s, and despite its popularity among the power theory, it has not been popular as a control algorithm. The article presents a control algorithm that works in accordance with the Fryze theory with non-linear load i.e. single-phase thyristor rectifier, which is a real challenge to verification of the control strategy. The simulation experiments were carried out using the well-known Simulink-Matlab program. the shape of the building, its mass and the appropriate insulation materials in the dry hot climate.